Soy protein isolate-based films cross-linked by epoxidized soybean oil. Issue 101 (29th September 2015) - Xia, Changlei; Wang, La; Dong, Youming; Zhang, Shifeng; Shi, Sheldon Q.; Cai, Liping; Li, Jianzhang
Abstract : Property enhancement of soy protein isolate-based film was achieved by introducing an environmentally friendly cross-linking agent, epoxidized soybean oil. Abstract : Epoxidized soybean oil (ESO) is an environmentally friendly cross-linking agent derived from soybean, having multiple epoxy groups in its molecules. It can effectively improve tensile strength and water resistance of soy protein isolate (SPI)-based films. The properties of the SPI-based films were characterized by X-ray diffraction and attenuated total reflectance Fourier transform infrared spectroscopy. The best performance of the SPI-based films was achieved when the ESO addition was 2.5%, for which tensile modulus, tensile strength and 10% offset yield strength were increased to 265.0 MPa, 9.8 MPa and 6.8 MPa, respectively. Compared to untreated SPI-based films, these were increases of 695.6%, 139.8%, and 246.6%, respectively. However, the elongation at break was decreased by 67.6% due to the cross-linking between SPI and ESO. The SPI-based film modified by 5% ESO had the best water-resistance property and reduced the 24 hour water absorption from 209.1% to 45.9%, which was a significant decrease of 78.1%.